Evidence and influence—Jimmy Smith on ways ILRI can balance global negative perceptions of livestock - Smith, Jimmy W. (International Livestock Research Institute, 2012)
On 22 June 2012, Peter Ballantyne interviewed ILRI Director General Jimmy Smith on global perceptions that livestock are not good for the planet - and what this means for ILRI. He argues that 'evidence' is at the heart of ILRI's contribution. We need better evidence of where livestock contributes positively and negatively, and we need to communicate this.